Training math teachers in Panamá: A mixed research (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The results of an evaluation process of a degree in teaching strategies implemented with elementaryschool mathematics teachers in Panama are presented. The degree course involved activities developed over 4months, based mainly on the problem-solving approach, contextualized activities and processes of reflection onteaching practice. The purpose was to provide teachers with tools for the design, implementation andimprovement of their didactic sequences. To evaluate the impact of this degree, the logical model of evaluationwas used and the results were analyzed in quantitative and qualitative areas. As a general result, reflectiveprocesses were presented and teachers were able to evaluate their teaching abilities, as well as their attitudes andmotivations regarding mathematics teaching, strengthening their disciplinary knowledge and didactic reflection.